2016
DOI: 10.1007/s40195-016-0512-0
|View full text |Cite
|
Sign up to set email alerts
|

Spark Plasma Sintering of Ultrafine YSZ Reinforced Cu Matrix Functionally Graded Composite

Abstract: Copper matrix composites have received more attentions as possible candidate for thermal and electrical conductive materials to be used in electrical contact applications. In this study, five-layered Cu/YSZ (yttria-stabilized zirconia) functionally graded material (FGM) and copper matrix composite specimens containing 3 and 5 vol% YSZ particles plus pure Cu specimen were synthesized using powder metallurgy (PM) route and spark plasma sintering (SPS) consolidation process. The microstructural and some physical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The fabricated FGCM was free from defects such as cracks, voids and delaminations. Ultrafine YSZ reinforced Cu matrix FGCMs were fabricated by Mirazimi et al [174]. The FGCM had five layers, and the maximum YSZ content was 5 vol.-%.…”
Section: Manufacturing Methods Of Fgcmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fabricated FGCM was free from defects such as cracks, voids and delaminations. Ultrafine YSZ reinforced Cu matrix FGCMs were fabricated by Mirazimi et al [174]. The FGCM had five layers, and the maximum YSZ content was 5 vol.-%.…”
Section: Manufacturing Methods Of Fgcmsmentioning
confidence: 99%
“…Data points for the thermal conductivity of pure W were collected from [248]. SiO 2 -Mo and Cu-YSZ FGCMs were studied by Honma and Tatami [173] and Mirazimi et al [174], respectively. Both studies reported an increase in the electrical resistivity with increasing ceramic content.…”
Section: Electrical Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of ceramics such as titanium carbide or alumina to copper increases its electrical resistivity and decreases the electrical conductivity [1]. The increase of lattice defects reduces the electron's mean free path and affects the electrical conductivity values [48]. This also can be explained by the zero electrical conductivity values of both TiC and Al2O3 which decreases the overall conductivity of the prepared composites [1].…”
Section: Electrical Conductivity Measurementmentioning
confidence: 99%
“…Among these, however, fine stabilized ZrO 2 ceramic particles could be a proper reinforcing material due to their high strength and stiffness, high melting temperature, and relatively good electrical property. 18 Although noticeable studies have been performed on the fabrication and characterization of ZrO 2 matrix composites reinforced with other ceramic materials, [19][20][21] the addition of ultrafine grained ZrO 2 particles to copper matrix and its subsequent effect on the microstructure, physical and mechanical properties as well as tribological behavior of copper matrix have been notified limitedly.…”
Section: Introductionmentioning
confidence: 99%